Autorzy:Dubiecka-Kruk Barbara, Dubiecka Anna, Bazyluk Anna
Wydawnictwo:WSiP
Rok wydania:2014
Oblicz 4.5 gwiazdek na podstawie 6 opinii

`a)\ (5^6*5^12):(5^4*5^6*5^3)=5^(6+12):5^(4+6+3)=5^18:5^13=5^(18-13)=5^5=5*5*5*5*5=25*25*5=625*5=3125`  

 

`b)\ (3^2*3^5*3^7):(3^4*3^5*3^3)=3^(2+5+7):3^(4+5+3)=3^14:3^12=3^(14-12)=3^2=3*3=9` 

 

`c)\ (2^10:2^7)*(2^18:2^14)=2^(10-7)*2^(18-14)=2^3*2^4=2^(3+4)=2^7=2*2*2*2*2*2*2=4*4*4*2=16*4*2=64*2=128`  

 

`d)\ (0,1^5*0,1^4*0,1^7)/(0,1^20:0,1^8)=(0,1^(5+4+7))/(0,1^(20-8))=(0,1^16)/(0,1^12)=0,1^(16-12)=0,1^4=0,0001` 

 

`e) \ ((-3)^12:(-3)^4)/((-3)^8:(-3)^3)=((-3)^(12-4))/((-3)^(8-3))=((-3)^8)/((-3)^5)=(-3)^(8-5)=(-3)^3=(-3)*(-3)*(-3)=9*(-3)=-27` 

`f)\ ((-2,5)^7:(-2,5)^2*(-2,5)^5)/((-2,5)^3*((-2,5)^2)^3)=((-2,5)^(7-2+5))/((-2,5)^3*(-2,5)^(2*3))=((-2,5)^10)/((-2,5)^(3+6))=((-2,5)^10)/((-2,5)^9)=(-2,5)^(10-9)=(-2,5)^1=-2,5`